CD10/Neprilysin Enrichment in Infrapatellar Fat Pad–Derived Mesenchymal Stem Cells Under Regulatory-Compliant Conditions: Implications for Efficient Synovitis and Fat Pad Fibrosis Reversal. Issue 8 (July 2020) - Kouroupis, Dimitrios; Bowles, Annie C.; Best, Thomas M.; Kaplan, Lee D.; Correa, Diego
Background: Synovitis and infrapatellar fat pad (IFP) fibrosis participate in various conditions of the knee. Substance P (SP), a neurotransmitter secreted within those structures and historically associated with nociception, also modulates local neurogenic inflammatory and fibrotic responses. Exposure of IFP mesenchymal stem cells (IFP-MSCs) to a proinflammatory/profibrotic environment (ex vivo priming with TNFα, IFNγ, and CTGF) induces their expression of CD10/neprilysin, effectively degrading SP in vitro and in vivo. Purpose/Hypothesis: The purpose was to test the therapeutic effects of IFP-MSCs processed under regulatory-compliant protocols, comparing them side-by-side with standard fetal bovine serum (FBS)–grown cells. The hypothesis was that when processed under such protocols, IFP-MSCs do not require ex vivo priming to acquire a CD10-rich phenotype efficiently degrading SP and reversing synovitis and IFP fibrosis. Study Design: Controlled laboratory study. Methods: Human IFP-MSCs were processed in FBS or either of 2 alternative conditions—regulatory-compliant pooled human platelet lysate (hPL) and chemically reinforced medium (Ch-R)—and then subjected to proinflammatory/profibrotic priming with TNFα, IFNγ, and CTGF. Cells were assessed for in vitro proliferation, stemness, immunophenotype, differentiation potential, transcriptional and secretory profiles, and SP degradation. Based on a rat model of acute synovitis and IFP fibrosis, the in vivo efficacy of cells degrading SP plus reversing structural signs of inflammation and fibrosis was assessed. Results: When compared with FBS, IFP-MSCs processed with either hPL or Ch-R exhibited a CD10 High phenotype and showed enhanced proliferation, differentiation, and immunomodulatory transcriptional and secretory profiles (amplified by priming). Both methods recapitulated and augmented the secretion of growth factors seen with FBS plus priming, with some differences between them. Functionally, in vitro SP degradation was more efficient in hPL and Ch-R, confirmed upon intra-articular injection in vivo where CD10-rich IFP-MSCs also dramatically reversed signs of synovitis and IFP fibrosis even without priming or at significantly lower cell doses. Conclusion: hPL and Ch-R formulations can effectively replace FBS plus priming to induce specific therapeutic attributes in IFP-MSCs. The resulting fine-tuned, regulatory-compliant, cell-based product has potential future utilization as a novel minimally invasive cell therapy for the treatment of synovitis and IFP fibrosis. Clinical Relevance: The therapeutic enhancement of IFP-MSCs manufactured under regulatory-compliant conditions suggests that such a strategy could accelerate the time from preclinical to clinical phases. The therapeutic efficacy obtained at lower MSC numbers than currently needed and the avoidance of cell priming for efficient results could have a significant effect on the design of clinical protocols to potentially treat conditions involving synovitis and IFP fibrosis.